2009
DOI: 10.1177/0149206309347957
|View full text |Cite
|
Sign up to set email alerts
|

Employee Retirement: A Review and Recommendations for Future Investigation

Abstract: Despite the obvious importance of retirement to employees, their employing organizations, and the larger society, the last comprehensive review of employee retirement in the field of organizational science was published more than 20 years ago. As such, the first purpose of this review is to provide a summary of key theoretical and empirical developments in employee retirement research since Beehr in 1986. A second purpose of this review is to highlight inconsistent findings revealed by studies that were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
768
2
37

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(834 citation statements)
references
References 177 publications
27
768
2
37
Order By: Relevance
“…Happiness would be more strictly related to well-being as a psychological status. Recent studies have included well-being in retirement in the dimension construct with satisfaction with financial status (Wang & Shultz, 2010), the time of retirement (Fadila & Alam, 2016), characteristics of previous work and the continuity of work (Bender, 2011).…”
Section: Satisfacción Con La Vida En Jubilados Que Permanecen Trabajandomentioning
confidence: 99%
“…Happiness would be more strictly related to well-being as a psychological status. Recent studies have included well-being in retirement in the dimension construct with satisfaction with financial status (Wang & Shultz, 2010), the time of retirement (Fadila & Alam, 2016), characteristics of previous work and the continuity of work (Bender, 2011).…”
Section: Satisfacción Con La Vida En Jubilados Que Permanecen Trabajandomentioning
confidence: 99%
“…One difficulty when studying the relationships between earlier life experiences and retirement is that the theoretical utility of the conceptualization of retirement as a rational decision-making process will be dependent upon the extent to which retirement transitions are the result of personal choice (Wang and Shultz 2010). Research has shown that many retirement transitions (around 25-30 percent) are perceived as forced or involuntary Davey 2005, Van Solinge andHenkens 2007).…”
Section: Retirement Decision-makingmentioning
confidence: 99%
“…In a recent review of the multidisciplinary retirement literature, Wang and Shultz (2010) have grouped the empirically studied predictors of retirement in four broad categories. Besides macro socio-economic factors (e.g., social security system, economic conditions), three groups of meso and micro level predictors of retirement are distinguished: individual attributes (e.g., age, health, financial resources), job and organizational factors (e.g., job characteristics, job attitudes), and family factors (e.g., marital status, dependent children, partner support).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on retirement over the last two decades has primarily focus on how planning for retirement influences retirement timing, post retirement satisfaction and adjustment. As a result, the theoretical conceptualizations most employed are retirement as decision making and retirement as adjustment (Wang & Shultz, 2010). For example, those who have prepared for retirement and feel ready to make the transition are more likely to exit the workforce at an earlier age (Reitzes, Mutran & Fernandez, 1998;Taylor & Shore, 1995).…”
Section: 0mentioning
confidence: 99%